Phenolic characterization of Northeast Portuguese propolis: usual and unusual compounds - Falcão, Soraia (2011)
In this study, an ethanolic extract from Portuguese propolis was prepared, fractionated by highperformance liquid chromatography, and the identification of the phenolic compounds was done by electrospray mass spectrometry in the negative mode. This technical approach allowed the identification of 37 phenolic compounds, which included not only the typical phenolic acids and flavonoids found in propolis from temperate zones but also several compounds in which its occurrence have never been referred to in the literature. Four of the novel phenolic compounds were methylated and/or esterified or hydroxylated derivatives of common poplar flavonoids, although six peculiar derivatives of pinocembrin/pinobanksin, containing a phenylpropanoic acid derivative moiety in their structure, were also identified. Furthermore, the Portuguese propolis sample was shown to contain a p-coumaric ester derivative dimer.